MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN PELAYANAN KARYAWAN PADA KONSUMEN DI PT. PLN (PERSERO) AREA MAKASSAR - Arfiany Arfiany (Jurnal Bisnis dan Kewirausahaan, 2016)
The purpose of this study was to determine whether the employee motivation effect on job satisfaction and quality of service at PT. PLN (Persero) Makassar Area? The research method used is quantitative method with the results showed that motivation significantly impact directly on job satisfaction. Motivation variable is formed by three indicators namely motives, expectations, and incentives show has managed so well that a meaningful contribution on employee job satisfaction. The results of statistical data analysis proves that there are significant direct effect of motivation on the quality of service of employees represented by the value of standardized direct effect of 0.673. This study found a significant direct influence between motivation of the quality of service of employees. This means that the better motivation of the employees then improving the quality of services provided by the employee PT. PLN (Persero) Makassar Area better anyway. And vice versa, if the employee motivation is low, the quality of service generated will be low. Job satisfaction significant effect on the quality of service of employees. Job satisfaction variables formed by three indicators, namely compensation, communication, and working conditions show has managed so well that a meaningful contribution to the quality of service provided by the employee, but to further improve the quality of services better according to the assessment of employees require attention in terms the suitability of allowances and bonuses as well as a harmonious relationship with colleagues.